The Effect of Patriarkat Ideology and the Relationship of Women’s Flores Towards Local Culture Preservation - Kebingin, Benedikta Yosefina; Martasudjita (Advances in Social Sciences Research Journal, 2021)
Research taken location in the region of Flores were in the paint with the culture of patriarchy is written under the theme "Influence of Ideology Patriarchate and the Women’s Keberperanana Flores on the Local Cultural Preservation". The life of the people of Flores has been well-established and strict in patriarchal culture since the time of the World War. In the course of time it cannot be denied that the way of viewing women and their involvement has certainly undergone some changes. Nevertheless, still needed an affirmation by deepening and cultural interpretation from time to time. The writer as a nun Congregation Imitationis Jesus (CIJ) has recorded the growth and development of women’s place in the Church and in Flores society. CIJ since inception and ala s an establishment atantion against women and its role. The role of the CIJ sisters for and with women struggles so that women have a place and opportunity to play a role in building lives according to their capacities. So in this writing used the method of library research with historical- theological approach. From the results of this study concluded that changing in gender equality discope patriarchal culture growing along with the climate of Christian life baby too new languages that were previously not commonly used, or which appear in a new way.